Singing Psalms with owls: A Venda 20th century musical history part two: tshikona, beer songs and personal songs - Kruger, Jaco (International Library of African Music, 2007)
The three categories of Venda music discussed here are tshikona (the bamboo pipe dance), beer songs (malende, jive) and personal songs. As I indicate in part One of this essay, tshikona is useful for the construction of a musical history because its performance is intimately associated with traditional politics. By contrast, beer songs do not feature directly in politics. However, they not only comprise the largest category of adult music, they also have more elaborate texts than Venda music forms such as tshikona or tshigombela.
Keywords: African Music